Knowledge claims in cognitive development research: Problems and alternatives. (December 2016) - Byers, Patrick
Abstract: Children's knowledge is often characterized in short propositional statements, e.g., a child may be claimed to know how counting works . This article analyzes the use of these knowledge claims in cognitive development research on children's understanding of numbers and counting. In this research, attempts to characterize children's knowledge in terms of knowledge claims are repeatedly invalidated by children's inconsistently normative uses of counting. This suggests that rather than describing cognitive structures/states, knowledge claims describe whether, in a certain domain, a person has a disposition to behave normatively (i.e., in a way that fits a consensually established standard of how things are appropriately done). Given that children's developing behavior is, by definition, inconsistently normative, knowledge claims can only characterize what research studies on children's conceptual knowledge presuppose—the incomplete normativity of children's behavior. Following the identification and explanation of this problem, several viable alternative approaches to the study of children's knowledge are described. The diversity of these alternatives reflects the need to disentangle descriptions from explanations, and discursive abstractions about cognitive processes from the processes themselves.